2021
DOI: 10.1002/acr.24143
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Gait Muscle Activation Patterns Differ for Osteoarthritis Patients Who Undergo Total Knee Arthroplasty Five to Eight Years Later From Those Who Do Not

Abstract: Objective. To determine if baseline quadriceps and hamstrings muscle activity patterns differed between those with medial-compartment knee osteoarthritis (OA) who advanced to total knee arthroplasty (TKA) and those who did not advance to TKA, and to examine associations between features extracted from principal component analysis (PCA) and discrete measures. Methods. Surface electromyograms of the vastus lateralis and medialis, rectus femoris, and lateral and medial hamstrings during walking were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Biomechanical studies have investigated the potential effects of muscle overactivity, typically quantifying this phenomenon using a co-contraction index [ 19 ]. Increased co-contraction has been linked to increased pain [ 20 ], elevated joint load [ 21 ], a more rapid rate of cartilage loss [ 22 ] and an increase in the likelihood that patients will opt for a knee replacement at 5-year follow up [ 23 ]. Given these findings, muscle overactivity is likely to increase the mechanical stress on the articular surface, the bone, joint capsule and periarticular structures and therefore may increase nociceptive input, exacerbating pain [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical studies have investigated the potential effects of muscle overactivity, typically quantifying this phenomenon using a co-contraction index [ 19 ]. Increased co-contraction has been linked to increased pain [ 20 ], elevated joint load [ 21 ], a more rapid rate of cartilage loss [ 22 ] and an increase in the likelihood that patients will opt for a knee replacement at 5-year follow up [ 23 ]. Given these findings, muscle overactivity is likely to increase the mechanical stress on the articular surface, the bone, joint capsule and periarticular structures and therefore may increase nociceptive input, exacerbating pain [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modelling studies have demonstrated a clear peak in joint loading during early stance [13] and also shown that elevated muscle activity, during this period, will increase contact force [13,14]. Other related research has shown that elevated muscle activity during the early stance period will accelerate cartilage loss [15] and increase the likelihood of progression to knee arthroplasty [16]. It is therefore critical to understand the mechanisms which underlie elevated muscle activity, in people with knee osteoarthritis, during early stance.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated co-contraction will increase stress on the articular surface, on the bone, joint capsule and periarticular structures, and is likely to increased pain [34]. These ndings indicate that co-contraction could be a potential intervention target [33].…”
Section: Discussionmentioning
confidence: 98%
“…Whereas in a healthy person these muscles activate sequentially during walking, in individuals with knee OA these muscles contract simultaneously during the stance phase of gait. Recent studies have demonstrated the potentially damaging effect of these patterns, showing that increased co-contraction will increase the compressive loads on the joint surface [31], speed up the rate of cartilage loss [32] and increase the likelihood that patients will opt for a knee replacement at 5-year follow up [33]. Elevated co-contraction will increase stress on the articular surface, on the bone, joint capsule and periarticular structures, and is likely to increased pain [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation